Peculiarities of matrix-element calculations with few Coulomb functions for particles' scattering processes - О, Chuluunbaatar; K.A, Kouzakov; A.G, Galstyan; Vu.V, Popov; M.S, Schoffler (Scientific transaction of the National University of Mongolia. Physics, 2022)
We present ultra high resolution data on single ionization of helium under impact of 1-MeV protons in comparison with theoretical calculations. Good agreement between theory and experiment [1] is obtained. Three initial trial helium wave functions are employed: a weakly correlated Roothaan-Hartree-Fock function, a simple Silverman-Platas-Matsen function of the configuration interaction family, and a strongly correlated function [2,3]. Multidimensional singular integrals which defining differential cross sections are calculated using special transform for each above trial function. Results of some calculations are presented in Figure 1.